Analysis of Constraints and Teachers’ Adaptive Teaching Strategies in Elementary School Physical Education with Limited Facilities - Muhammad Kantaqa; Dinar Dinangsit; Encep Sudirjo (Universitas Negeri Semarang, 2026)
Limited facilities and infrastructure remain a common issue in the implementation of Physical Education, Sports, and Health (PE) learning in elementary schools. These limitations may affect the effectiveness of learning activities and students’ participation in physical education. This study examines the challenges encountered and the adaptive teaching strategies employed by teachers in the implementation of Physical Education, Sports, and Health (PE) learning in schools with limited facilities. This study employed a qualitative approach with a case study design at Pangadegan Elementary School to explore the phenomenon in its real context. Data collection was conducted by interviews, observations and documentation. Data analysis was conducted through the stages of data reduction, data presentation and conclusion development. The results indicate that the main challenges are linked to the limited access to sports fields, insufficient equipment and limited space for students to move, which leads to less optimal learning activities. To meet these challenges, teachers applied adaptive strategies, such as changing the location of learning activities, adjusting games, and adapting learning materials to the conditions available. The role of the school principal in facilitating learning management also supports the effectiveness of these strategies. However, students showed high enthusiasm in participating in learning activities, but they still had difficulties in motor skill performance. These results show that the success of Physical Education learning is determined not only by the availability of facilities, but also by the adaptability and support from the school teachers.